Altered Microstructure Within Social-Cognitive Brain Networks During Childhood in Williams Syndrome. (24th May 2013) - Haas, Brian W.; Barnea-Goraly, Naama; Sheau, Kristen E.; Yamagata, Bun; Ullas, Shruti; Reiss, Allan L.
Abstract : Williams syndrome (WS) is a neurodevelopmental condition caused by a hemizygous deletion of ∼26–28 genes on chromosome 7q11.23. WS is associated with a distinctive pattern of social cognition. Accordingly, neuroimaging studies show that WS is associated with structural alterations of key brain regions involved in social cognition during adulthood. However, very little is currently known regarding the neuroanatomical structure of social cognitive brain networks during childhood in WS. This study used diffusion tensor imaging to investigate the structural integrity of a specific set of white matter pathways (inferior fronto-occipital fasciculus [IFOF] and uncinate fasciculus [UF]) and associated brain regions [fusiform gyrus (FG), amygdala, hippocampus, medial orbitofrontal gyrus (MOG)] known to be involved in social cognition in children with WS and a typically developing (TD) control group. Children with WS exhibited higher fractional anisotropy (FA) and axial diffusivity values and lower radial diffusivity and apparent diffusion coefficient (ADC) values within the IFOF and UF, higher FA values within the FG, amygdala, and hippocampus and lower ADC values within the FG and MOG compared to controls. These findings provide evidence that the WS genetic deletion affects the development of key white matter pathways and brain regions important for social cognition.